Characterization of epiretinalmacrophage-like cells and retinochoroidal blood flow in acute macular neuroretinopathy - YANG Ruijun; WEN Feng; ZHANG Xiongze (Yanke Xuebao)
[Objective:] To investigate the clinical characteristics of epiretinal macrophage-like cells (eMLC) and retinochoroidal blood flow in eyes affected by acute macular neuroretinopathy (AMN). [Methods:] This retrospective case series study included 21 (37 eyes) patients diagnosed with AMN and 28 (33 eyes) healthy age-matched subjects. A 3 mm En-face optical coherence tomography (OCT) slab on the inner limiting membrane of the macular region was used to visualize and binarize the MLCs. The MLCs were binarized and quantified using a semiautomated method. Optical coherence tomography angiography (OCTA) was used to evaluate the perfusion status and obtain the structural data of macular within a 6 x 6 mm2 macular region. [Results:] The number and density of macular eMLC in AMN eyes were significantly increased in comparison to control eyes: 329.78±77.38 vs. 202.63±41.72, (P<0.001) and (9.16±2.15) cells/mm2 vs. (5.63±1.16) cells/mm2 (P<0.001). In the macular region, both superficial and deep retinal vessel densities were significantly lower in the AMN eyes than in the control eyes: (33.00±6.49)% vs. (36.18±5.63)%(P=0.040); (32.59±7.41)% vs. 37.08±5.65 (P=0.008). There were no significant differences in the vessel densities and foveal avascular zone (FAZ) area of full retina and choroidal vessel density between the two groups (P>0.05). The eMLC density was not associated with the superficial and deep retinal FAZ area and vessel densities (all P>0.05). At the one-month follow-up data of 13 patients (23 eyes), the number and density of macular eMLC were significantly lower in comparison to the initial visit: 248.70±59.88 vs. 307.87±82.98, P<0.001 and (6.91±1.66) cells/mm2 vs. (8.55±2.30) cells/mm2 (P<0.001). However, the number and density of macular eMLC are still noticeably higher than those of the control group during the same timeframe: 248.70±59.88 vs. 176.58±27.89 (P<0.001) and (6.91±1.66) cells/mm2 vs. (4.91±0.77) cells/mm2 (P<0.001). There was no significant difference in the vessel density of retina and choroidal during the follow-up (P>0.05). [Conclusions:] The aggregation and activation of eMLC and a mild decrease in retinal blood flow density are observed in AMN, yet there is no corresponding shift in choroidal vessel density. The changes of eMLC are linked to the course of AMN, but they are not related to retinal vessel density. The inflammatory response represented by eMLC might independently contribute to the pathogenesis and progression of AMN.